Analisis Kinerja Remote Server Administrator untuk Managemen Jaringan Komputer - Agung Priyamanto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
In the computer networking world, administration and configuration in a UNIX based server are usuallyperformed in terminal or shell in which administrator interact with the server. This is common for administratorthat is used to interact with Command Line Interface or shell. For those who have not used to it will have agreat obstacle to deal with . Thus, there are many people created web based application to perform admnitrationon UNIX server such as webmin. But, o have web based network manajement application, a server must has webserver services.This prequisite will not be a problem for a server that is designed to perform web application.But for dedicated server having services not web application, it will bring a compromise in considerationespecially in security and reliability issue. Additional web application will bring concequences to open severalport. That is obviously incereases server vulnerability. In other hand, additional web application will take someresources of a server which are actually designed for certain services. Thus, our previous research has promotean RSA application to manage a server. RSA is web application to manage remote servers. Connection betweenuser and RSA performed using http port while connection between RSA and remote server performed using SSHport. So, a server doesn’t have to open additional port except SSH port that is ussualy already opened foradministration purpose RSA was developed using CGI-PERL script with APACHE as it web server. Severalservices that can be configure using this RSA are APACHE web server, BIND name server and SQUID proxyserver. Unfortunately, after observing this application further, we found that this solution has it’s owndisadvantages. This paper will speak about the result of RSA application analysis.Keywords: RSA,Network Analysis, Network Management, Server Adninistration